Multilingualism as a Resource in the Foreign Language Classroom: A Study on Utilizing the Language Backgrounds of Multilingual Children in Finnish Comprehensive School - Illman, Veera (My University, 2017)
In this MA thesis, multilingual children of immigrant background as well as English teachers were studied. The purpose of the study was to examine how much and in what ways children of immigrant background take advantage of their multilingualism in foreign language learning. On the other hand, the study investigated how multilingual children’s language backgrounds were taken into account in English classrooms, and what the teacher perceptions were of how the learning process of immigrant children could be supported. The data were collected with two questionnaires – one questionnaire was constructed for students and one for teachers. 55 multilingual students and 38 English teachers form the sample in this study, and both quantitative and qualitative data were received from their answers. The results showed that the students had very positive attitudes towards their own multilingualism, and they were able to recognize how multilingualism could benefit them later in life. It also seemed that many students used their native languages as a resource in learning English, for example by comparing vocabularies or looking for similarities and differences between the languages. Teachers had not received much training related to working with multilingual students, which resulted in linguistic challenges in their work. The teachers were able to see multilingualism as something that supports foreign language learning, but on the other hand the lack of shared language and the students’ weak Finnish skills created challenges according to the teachers. Based on these results, it seems that teachers are in need of more training on supporting multilingual learners, and that more research is needed to gain a deeper understanding on the ways in which multilingual students utilize their linguistic backgrounds in foreign language learning. This would both support teachers in their work, and help multilingual students achieve better learning results.